2016
DOI: 10.1080/13880209.2016.1238949
|View full text |Cite
|
Sign up to set email alerts
|

Meisoindigo, but not its core chemical structure indirubin, inhibits zebrafish interstitial leukocyte chemotactic migration

Abstract: Context: Inflammatory disease is a big threat to human health. Leukocyte chemotactic migration is required for efficient inflammatory response. Inhibition of leukocyte chemotactic migration to the inflammatory site has been shown to provide therapeutic targets for treating inflammatory diseases.Objective: Our study was designed to discover effective and safe compounds that can inhibit leukocyte chemotactic migration, thus providing possible novel therapeutic strategy for treating inflammatory diseases.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A recent study indicates that meisoindigo was also found to downregulate the TLR4-TAK-NF-κB pathway, which played critical roles in inflammatory cytokines release (Zhang et al, 2013). In addition, we previously showed that meisoindigo inhibits leukocyte chemotactic migration, which plays a critical role in the inflammatory response (Ye et al, 2017). These observations led us to conjecture that meisoindigo might regulate the immune response via TLR4/NF-κB mediated inflammatory signaling following stroke.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent study indicates that meisoindigo was also found to downregulate the TLR4-TAK-NF-κB pathway, which played critical roles in inflammatory cytokines release (Zhang et al, 2013). In addition, we previously showed that meisoindigo inhibits leukocyte chemotactic migration, which plays a critical role in the inflammatory response (Ye et al, 2017). These observations led us to conjecture that meisoindigo might regulate the immune response via TLR4/NF-κB mediated inflammatory signaling following stroke.…”
Section: Introductionmentioning
confidence: 93%
“…Meisoindigo is significantly more resistant to protein kinases and exhibits higher antitumor activity than indirubin. Meisoindigo has numerous biological effects, including anti-neoplastic (Cheng et al, 2016), anti-inflammatory (Zhang et al, 2013) and antileukocyte chemotactic effects (Ye et al, 2017). However, whether meisoindigo exerts a neuroprotective action in ischemic stroke remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The specific NLRP3 inflammasome inhibitor MCC950 significantly improved neurologic outcomes and reduced infarct volume when administered before or after MCAO 436 . Studies have also shown that meisoindigo, a generally water soluble and well‐tolerated second‐generation indirubin derivative, reduces inflammation by inhibiting leukocyte chemotaxis and migration 437,438 . Meisoindigo posttreatment alleviates brain damage induced by ischemic stroke in vivo and in in vitro model experiments through blocking the activation of the NLRP3 inflammasome 439 .…”
Section: Potential Neuroprotective Targets For Ischemic Stroke Therapymentioning
confidence: 99%
“…In addition, structure-function studies have been performed using this model. For example, meisoindigo, which is a derivative of indirubin, a chemical constitute of the traditional Chinese herbal medicine Qing Dai was found to inhibit leukocyte migration induced by tail wounding without affecting reverse migration or Akt and Erk activity, whereas indirubin (which represents the core structure of meisoindigo) did not show an effect (Ye et al, 2017 ). Moreover, a particular chemical group, consisting of fused benzene and pyran rings with an attached carbonyl group (1,4-benzopyrone) or its isomer “coumarin” (1-benzopyran-2-one), was found to be present in four of the nine most-active pro-resolution compounds identified in a large screen of 2,000 well-characterized and approved drugs.…”
Section: Inflammatory Disease Models In Zebrafishmentioning
confidence: 99%